Relationship between training framing and trainees' training effectiveness : the moderating role of self-efficacy - Edward Munovah, Bridget Michel (University Malaysia Sarawak, (UNIMAS), 2009)
This study was conducted to determine the moderating role of self-efficacy in the relationship between training framing and trainees’ training effectiveness. A survey research method was used to gather 120 usable questionnaires from employees in Sarawak Information System Sdn. Bhd. (SAINS) Training Centre and Jabatan Kerja Raya (JKR). The respondents were trainees who attended computer and machine related training programme. The outcome of hierarchical regression analysis shows that self-efficacy strengthened the relationship between training framing and trainees’ training effectiveness. This result shows that self-efficacy act as a moderator in the relationship between training framing and trainees’ training effectiveness. Besides, implications to theories show that this study was in line with research done by Tai (2006) and supported by research done by Chiaburu and Tekleab (2005). Recommendations for future research are also discussed in this study.